2012
DOI: 10.4236/abb.2012.33030
|View full text |Cite
|
Sign up to set email alerts
|

An animal cell culture: Advance technology for modern research

Abstract: At the present time animal cell culture is more significant and multifarious application tool for current research streams. A lot of field assorted from animal cell culture such: stem cell biology, IVF technology, cancer cell biology, monoclonal antibody production, recombinant protein production, gene therapy, vaccine manufacturing, novel drug selection and improvement. In this review conclude animal cell culture as well as its requirement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…In early days, natural media such as biological fluids (plasma, serum, lymph, amniotic fluid etc. ), tissue extract (extract of chick embryo, liver, spleen, bone marrow and leucocytes) obtained from various biological sources were used to establish cell culture (Shenoy, 2007;Nema and Khare, 2012). The major disadvantage of using natural media is that it often results in poor reproducibility in cell culture due to lack in knowledge about its exact composition.…”
Section: Role Of Nutrients and Other Factors Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…In early days, natural media such as biological fluids (plasma, serum, lymph, amniotic fluid etc. ), tissue extract (extract of chick embryo, liver, spleen, bone marrow and leucocytes) obtained from various biological sources were used to establish cell culture (Shenoy, 2007;Nema and Khare, 2012). The major disadvantage of using natural media is that it often results in poor reproducibility in cell culture due to lack in knowledge about its exact composition.…”
Section: Role Of Nutrients and Other Factors Mediamentioning
confidence: 99%
“…Cultured cells, either as short term or as established cell lines, from a broad range of tissues and organs have many applications in fundamental and applied biological research (Keay, 1975;Hightower and Renfro, 1998;Marrec-Croq et al, 1999;Butler, 2005;Nema and Khare, 2012). These in vitro models form the biological basis of most alternative methods (Hartung, 2007) and are used to study cell differentiation, toxicology and pharmacology, cancer research thereby avoiding the use of laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture is important for the evaluation of cell physiology and cellular responses to pharmaceutical compounds (1,2). Many cell lines have been established and cultured in appropriate media such as minimum essential medium (MEM), Dulbecco's Modified Eagle Medium (DMEM), and RPMI-1640.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that growing tissues of living organism outside the body are made possible in an appropriate culture medium, containing a mixture of nutrient either in solid or liquid form. At present significant progress has been made in the field of animal cell culture [1,2]. Generally a growth medium or cell culture medium is developed to assist the growth of microorganisms or cells [3].…”
Section: Introductionmentioning
confidence: 99%